PTH-275 Restaging after neoadjuvant chemoradiation in rectal cancers – is histology the key in patient selection?. (22nd June 2015) - Vallam, KC; Singhal, N; Arya, S; Engineer, R; Ostwal, V; Saklani, A
Abstract : Introduction: Neoadjuvant chemoradiation is the standard of care for locally advanced rectal cancer. However, there is no clarity regarding the necessity for restaging scans to rule out systemic progression of disease post chemoradiation with existing literature being divided on the need for the same. Method: Data from a prospectively maintained database was retrospectively analysed. All locally advanced rectal cancers (Node positive/T4/T3 with threatened or involved CRM) were included. Biopsy proof of adenocarcinoma and CT scan of abdomen and chest were mandatory for inclusion. Grade of tumour and response to chemoradiation (CTRT) on restaging MRI were documented. Results: Out of 119 patients subjected to CTRT, 72 underwent definitive total mesorectal excision while 13 patients progressed locoregionally on restaging MR pelvis and 15 other patients progressed systemically while 15 patients defaulted and 4 patients did not complete radiation. Patients with poorly differentiated (PD) cancers were compared to those with well/moderately differentiated (WMD) tumours. PD tumours had a significantly higher rate of local progression (32.1% vs. 5.6%%, p = 0.0011) and systemic progression (35.7% vs. 6.9%, p = 0.0008) as compared to WMD tumours. Only one-third (9/28) of PD patients underwent TME while the rest progressed. Conclusion: Selecting poorly differentiated tumours alone for restaging CECT abdomen and thorax will be a cost effective strategy as the rate of progression is very high. Also patients with PD tumours need to be counselled about the high probability of progression of disease. Disclosure of interest: None Declared.